2007
DOI: 10.1111/j.1740-8709.2007.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a new food frequency questionnaire for pregnant women in the Norwegian Mother and Child Cohort Study (MoBa)

Abstract: The aim of the present study was to examine the relative validity of foods and nutrients calculated by a new food frequency questionnaire (FFQ) in the Norwegian Mother and Child Cohort Study (MoBa). Reference measures were a 4-day weighed food diary (FD), a motion sensor for measuring total energy expenditure, one 24-h urine collection for analysis of nitrogen and iodine excretion, and a venous blood specimen for analysis of plasma 25-hydroxy-vitamin D and serum folate. A total of 119 women participated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
237
5
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 236 publications
(272 citation statements)
references
References 42 publications
28
237
5
2
Order By: Relevance
“…Dietary intake was obtained from a semiquantitative food frequency questionnaire developed specifically for the MoBa, and administered in the 22nd week of pregnancy 29. The MoBa food frequency questionnaire has been validated in substudies using a 4‐day weighted food diary, motion sensors, and biological markers 30, 31. A poor diet quality indicator variable was created on the basis of having a high sodium/potassium ratio (top quartile, ≥0.88) or a low dietary calcium or low magnesium intake (<736 or <310 mg/d, respectively) given the available evidence of their importance in hypertension 32, 33, 34.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary intake was obtained from a semiquantitative food frequency questionnaire developed specifically for the MoBa, and administered in the 22nd week of pregnancy 29. The MoBa food frequency questionnaire has been validated in substudies using a 4‐day weighted food diary, motion sensors, and biological markers 30, 31. A poor diet quality indicator variable was created on the basis of having a high sodium/potassium ratio (top quartile, ≥0.88) or a low dietary calcium or low magnesium intake (<736 or <310 mg/d, respectively) given the available evidence of their importance in hypertension 32, 33, 34.…”
Section: Methodsmentioning
confidence: 99%
“…FoodCalc (35) and the Norwegian food composition table (36) were used to calculate food and nutrient intakes. The FFQ has been extensively validated in a MoBa sub-population (n 119) using a 4 d weighed food diary and biological markers in blood and urine as reference measures (37) . The validation study showed that the MoBa FFQ is a valid instrument for assessing habitual diet during the first four to five months of pregnancy.…”
Section: Dietary Informationmentioning
confidence: 99%
“…Assessments of other food, nutrient, and energy intakes during the pregnancy were based on data from a semiquantitative food frequency questionnaire specifically developed and validated for pregnant women in MoBa (Q2 at 22 weeks of pregnancy, where average intakes during the first half of pregnancy were reported, described in detail elsewhere) (Brantsaeter, Haugen, Alexander, & Meltzer, 2008, Meltzer, Brantsaeter, Ydersbond, Alexander, & Haugen, 2008). Energy intake from protein, fat, carbohydrates, added sugar, and SSC, and intake of micronutrients (vitamins and minerals) was calculated from food frequencies using FoodCalc (Lauritsen, 2002) and the Norwegian Food Composition Table (Rimestad et al, 2001).…”
Section: Participants and Methodsmentioning
confidence: 99%